Opening up #jesuisCharlie. Anatomy of a Twitter discussion with mixed methods - Johansson Marjut; Kyröläinen Aki-Juhani; Ginter Filip; Lehti Lotta; Krizsán Attila; Laippala Veronika (Elsevier, 2022)
•
The analysis was based on a large-scale corpus of tweets in English in the Twitter discussion with the hashtag #jesuisCharlie.
•
The analysis was conducted sequentially with mixed methods: language technology method, quantitative analysis of modality, and digital discourse analysis of the opinions expressed in the tweets.
•
The data contained multiple topics that were organized into five clusters.
•
One of the clusters was more modalized than others.
•
All of the clusters contained expressions of affectivity and solidarity, but they also contained diversified and polarized opinions.